1984
DOI: 10.1111/j.1432-1033.1984.tb08090.x
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxic properties of chemically synthesized lipid A part structures. Comparison of synthetic lipid A precursor and synthetic analogues with biosynthetic lipid A precursor and free lipid A

Abstract: Synthetic lipid A part structures corresponding structurally to a biosynthetic lipid A disaccharide precursor have been analyzed for endotoxic activity in several systems in vivo and in vitro.It was found that a synthetic P-1,6-linked D-glucosamine disaccharide, which carries four molar equivalents of (R)-3-hydroxytetradecanoyl residues in positions 2, 3, 2' and 3' and phosphoryl groups in positions 1 and 4' (preparation 406), exhibited lethal toxicity, B lymphocyte mitogenicity, the capacity to engender prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
1
2

Year Published

1984
1984
2006
2006

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 170 publications
(88 citation statements)
references
References 20 publications
5
80
1
2
Order By: Relevance
“…First, the lipid A from Salmonella LPS is specifically inactive on human cells, showing that recognition of the lipid A structure by human cells is different from that of mice or rabbits. The same species-specific phenomenon had been observed with tetraacylated lipid A precursor (lipid IV A ), which is also active in mice and rabbits, but inactive on human cells (9,33). However, the meaning of these two lipid As is completely different in view of the fact that the precursor structure is an intermediate in the biosynthesis of LPS, whose structure is not found as a component of any LPS.…”
Section: Discussionmentioning
confidence: 84%
“…First, the lipid A from Salmonella LPS is specifically inactive on human cells, showing that recognition of the lipid A structure by human cells is different from that of mice or rabbits. The same species-specific phenomenon had been observed with tetraacylated lipid A precursor (lipid IV A ), which is also active in mice and rabbits, but inactive on human cells (9,33). However, the meaning of these two lipid As is completely different in view of the fact that the precursor structure is an intermediate in the biosynthesis of LPS, whose structure is not found as a component of any LPS.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, all structural elements required for the induction of these endotoxin activities are present in the lipid A precursor indicating that for these effects 3-acyloxyacyl groups are not important. The bacterial and synthetic precursor molecules were, however, found to be of weak pyrogenicity and to be incapable of preparing for or eliciting the local Shwartzman reaction [30,311. This suggests that the presence of 3-acyloxyacyl groups is necessary for the full expression of these endotoxic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…This structure has recently been chemically synthesized [29] and been analysed biologically in comparison with the natural lipid A precursor and bacterial free lipid A in various endotoxin tests. It was found that the bacterial and synthetic precursor exhibit strong activities in a number of systems in vivo and in vitro including lethal toxicity, B-lymphocyte mitogenicity and the capacity to activate macrophages [30,311. Thus, all structural elements required for the induction of these endotoxin activities are present in the lipid A precursor indicating that for these effects 3-acyloxyacyl groups are not important.…”
Section: Discussionmentioning
confidence: 99%
“…The revised structure was based on the studies by high resolution mass spectrometry and two-dimensional nuclear magnetic resonance [I 3 -151. The newly synthesized analogues were mainly distributed to three groups in Tokyo (this study), Osaka [25] and Freiburg [26] and each group independently investigated biological activities, some common to the groups but some not.…”
Section: Discussionmentioning
confidence: 99%